Identification of mutations in Colombian patients affected with Fabry disease (2015)
Fabry Disease (FD) is an X-linked inborn error of glycosphingolipid catabolism, caused by a deficiency of the lisosomal ?-galactosidase A (AGAL). The disorder leads to a vascular disease secondary to the involvement of kidney, heart and the central nervous system. The mutation analysis is a valuable tool for diagnosis and genetic counseling. Although more than 600 mutations have been identified, most mutations are private. Our objective was to describe the analysis of nine Colombian patients with Fabry disease by automated sequencing of the seven exons of the GLA gene. Two novel mutations were identified in two patients affected with the classical subtype of FD, in addition to other 6 mutations previously reported. The present study confirms the heterogeneity of mutations in Fabry disease and the importance of molecular analysis for genetic counseling, female heterozygotes detection as well as therapeutic decisions. © 2015 Elsevier B.V.